Hubungan Kecemasan, Depresi dan Harga Diri dengan Kualitas Hidup pada Pasien Penyakit Gagal Ginjal Kronik yang Menjalani Hemodialisis - Sasteri Yuliyanti; Hasanah, Uswatun; Rustandi, Handi (STIKes Hamzar, 2025)
Renal failure is a progressive and irreversible disorder of renal function, in which kidney function decreases. Hemodialysis is a therapy for patients with chronic renal failure, where anxiety, depression, and self-esteem are psychological reactions that are often experienced this condition can affect the patient's quality of life. Aim: This study aims to determine the correlation between anxiety, depression, and self-esteem with quality of life in patients with chronic renal failure undergoing hemodialysis at RSUD Rejang Lebong in 2024. Method: This study uses descriptiveanalysis with a cross sectional approach. The data used is primary data and secondary data. To determine the value of anxiety, depression, self-esteem and quality of life using a questionnaire. The data was analyzed using the chi squaretest. Result: The results of the study using the Chi Square test showed that there was a correlation between anxiety, depression, and self-esteem with quality of life in patients with chronic renal failure undergoing hemodialysis at RSUD Rejang Lebong in 2024 with a p value of p = ≤ 0.05. Conclusion: The conclusion in this study is that the quality of life of chronic renal failure patients is influenced by the level of anxiety, depression, and self-esteem.